In search of fair unit rate terminal navigation charge for soekarno hatta airport & halim airport using activity based costing system at airnav indonesia - Ahmad Junaedi, Rahayu; Aliludin, Arson (The Indonesian Journal of Business Administration, 2019)
Abstract. Current Air Navigation Charge system does not fully apply the concept of cost recovery that become the main base of financial management in AirNav Indonesia according to President Decree No 77 of 2012. One of the proofs is that the Terminal Navigation Charge structure is based on three categories: Precision, Non-Precision, and Information. This research is conducted in search of fair unit rate terminal navigation charge which is comply with cost recovery using activity-based costing system. Soekarno Hatta and Halim Airport are chosen as the research location because both airports have completely different operational complexity yet but both are in same category of terminal navigation charge, precision category with the unit rate of Rp.5.500. Result of this research found that the unit rate of Soekarno Hatta Airport is Rp.22.273 for domestic flight and Rp.21.305 for international flight; meanwhile the unit rate of Halim Airport is Rp.47.732 for domestic flight and Rp.45.658 for international flight. Based on analysis of total costs needed to hold the terminal navigation charge in those airports, there is still deficit of Rp. 389,32 M by applying current unit rate. However, when applying the new unit rate, those cost will be fully covered.Those new unit rate is still under the unit rate that is stipulated in AirServices Australia that has operational similarities with AirNav Indonesia as well. By applying the new unit rate for Soekarno Hatta Airport, operational cost of flight Airbus 320 with 1-hour flight hour will increase 1.55% for domestic flight and 1.14% for international flight, that will gradually decrease as the flight hour increases. Applying the new unit rate will also increase the ticket price of flight Airbus 320 of Rp.11.415 per passenger for domestic flight and Rp.9.061 per passenger for international flight for flight load factor 60%, whereas the impact will gradually decrease as the flight load factor increases. Based on research result and the corresponding analysis, so the new determined unit rate is more reasonable and apply fairness for the stakeholders.Keywords: terminal navigation charge, PCN, PCF, ABC System, Cost Recovery